2015
DOI: 10.1212/wnl.0000000000001588
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress is related to disease severity in the ALS motor cortex

Abstract: (62)Cu-ATSM PET imaging demonstrated increased oxidative stress based on an over-reductive state, primarily in the motor cortex, in patients with ALS. The magnitude of oxidative stress correlated well with clinical severity, indicating that it may be associated with neurodegenerative changes in ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 35 publications
6
107
0
Order By: Relevance
“…22 A marker of oxidative stress, 62 Cu-diacetyl-bis (N4-methylthiosemicarbazone), was found to be reduced in cell lines with mitochondrial respiratory failure and in specific brain areas of patients with ALS, showing a correlation between its retention rate and the clinical severity estimated using the revised ALS Functional Rating Scale score. 22 These findings were also confirmed by studies that demonstrated increased oxidative damage in post-mortem tissues from patients with ALS, such as high levels of protein carbonyls in the spinal cord and motor cortex of the affected patients compared with the control group. 23,24 Unfortunately, the current patient refused to undergo a lumbar puncture, so it was not possible to present her cerebrospinal fluid data.…”
Section: Discussionmentioning
confidence: 99%
“…22 A marker of oxidative stress, 62 Cu-diacetyl-bis (N4-methylthiosemicarbazone), was found to be reduced in cell lines with mitochondrial respiratory failure and in specific brain areas of patients with ALS, showing a correlation between its retention rate and the clinical severity estimated using the revised ALS Functional Rating Scale score. 22 These findings were also confirmed by studies that demonstrated increased oxidative damage in post-mortem tissues from patients with ALS, such as high levels of protein carbonyls in the spinal cord and motor cortex of the affected patients compared with the control group. 23,24 Unfortunately, the current patient refused to undergo a lumbar puncture, so it was not possible to present her cerebrospinal fluid data.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we demonstrated increased uptake of 62 Cu-ATSM in brain lesions in a patient with MELAS syndrome [9], and in the cerebral motor cortex in patients with ALS [10, 11]. We also found increased striatal uptake of 62 Cu-ATSM in patients with PD in our previous study [12], which showed a significant, but slightly weak correlation between 62 Cu-ATSM SUVR for the bilateral striata and the UPDRS total score ( r  = 0.52, p  < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…We developed an imaging technique for an intracellular over-reductive state caused by mitochondrial respiratory failure to delineate regional oxidative stress in living patients, positron emission tomography (PET) imaging with [ 62 Cu]diacetyl-bis( N 4 -methylthio-semicarbazone) ( 62 Cu-ATSM) [7, 8]. 62 Cu-ATSM PET imaging successfully demonstrated a large retention of the ligand in the brains of patients with an inherited mitochondrial disorder, mitochondrial myopathy, encephalopathy, lactic acidosis, stroke-like episodes (MELAS) syndrome [9], and amyotrophic lateral sclerosis (ALS) [10, 11]. Also in PD, 62 Cu-ATSM PET imaging showed that striatal uptake was greater in patients than healthy controls and increased with the clinical severity of the disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of neuronal mitochondria has been suggested to play an important role in MN degeneration [20]. The oxidative and endoplasmic reticulum (ER) stress [16,17] and deregulation of the ER mitochondrial calcium cycle [22] are described as the most likely causes of motor neuronal death, but it is believed that a complex mechanism of multiple toxic pathways is implicated in the ALS onset and progression [32]. Glutamate-induced excitotoxicity is also considered as one of the possible pathophysiological factors of motor neuron death [4,12].…”
Section: Discussionmentioning
confidence: 99%